Grundpremisser för dialogisk musikanalys - Moisala, Pirkko (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2003)
Basic Premises for Dialogic Music Analysis The dialogic approach to music analysis, which is introduced in this article, addresses the ontology of musical works providing an alternative point of departure to score analysis. It is argued that “music” or “a musical work” is not located in one place, for instance in the score, in the intentions of the composer or in the performance, but in a network consisting of various meanings attached to them by these and other “authors” of the work. Respectively, the result of an analytical interpretation is understood only as a construction, as one “voice” taking part in the “work” discourse. The research material for this kind of analysis comprises all the acts which give meanings to the works/music in question, including performances and different verbalizations of it. This kind of dialogic approach to contemporary musical works corresponds with ideas presented within postmodern musicology but it is also related to traditional ethnomusicology, which has suggested that music should be studied as a contextual phenomenon, and the makers of music, creators/composers, listeners, musicians should be approached as informants/agents of music. In order to know what music is, the scholar has to listen carefully to the music-makers and learn about their apprehension of music. The dialogic approach to musical works provides a fruitful base for the ethno-theoretical study of contemporary art music. Interviews with the composer and other authors of music (performers, sound technicians), as well as previous literary sources combined with careful examination of musical works, reveal how the understanding that music/musical work is always constructed anew by different authors. The work “lives” in an intertextual space, within a network of associated meanings.